Development and Validation of Integrated Yoga Module for Hypertension - K S Nibedita; Suchitra S Patil; Amit Singh; R. Nagarathna (International Journal of Yoga)
Objectives: Hypertension (HTN), a lifestyle disorder, is characterized by elevated blood pressure and autonomic imbalance. Material and Methods: There is a bidirectional association between anxiety, depression, and HTN. Studies have reported the beneficial role of yoga in alleviating the symptoms of HTN; however, a validated integrated yoga module (IYM) for HTN is unavailable. The objective of this study was to develop and validate an IYM for HTN. The IYM was prepared after a thorough review of classical yoga texts and publications on yoga/meditation for HTN. Results: Twenty experienced yoga experts, who fulfilled the inclusion criteria, were selected for validating the content of the IYM. Conclusion: A total of 31 practices were included in the IYM, and the experts were requested to rate each practice as (i) not essential, (ii) useful but not essential, and (iii) essential; the content validity ratio (CVR) was calculated using Lawshe’s formula. Out of 31 practices, 4 practices had the least CVR ratio (45 for a 20 expert panel) with a mean CVR of 0.68. This IYM for HTN has good content validity.